2013
DOI: 10.1016/j.bbrc.2012.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibition of mTORC1 activation, DNA synthesis and proliferation in pancreatic cancer cells: Dependence on glucose concentration and role of AMPK

Abstract: Metformin, a widely used anti-diabetic drug, is emerging as a potential anticancer agent but the mechanisms involved remain incompletely understood. Here, we demonstrate that the potency of metformin-induced AMPK activation, as shown by the phosphorylation of its substrates acetyl-CoA carboxylase (ACC) at Ser79 and Raptor at Ser792, was dramatically enhanced in human pancreatic ductal adenocarcinoma (PDAC) cells PANC-1 and MiaPaCa-2 cultured in medium containing physiological concentrations of glucose (5mM), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
88
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 33 publications
1
88
0
Order By: Relevance
“…ple, metformin inhibited constitutive and induced activation of mTOR in several pancreatic cancer cell lines, and the inhibitory effects were higher in cells grown in normal 5 mM glucose as compared with cells cultured in 25 mM glucose (19,23,24). It has also been reported that metformin suppresses the IGF-1R and mTOR signaling in pancreatic cancer cells, and this contributes to the antineoplastic activity of this agent (19).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…ple, metformin inhibited constitutive and induced activation of mTOR in several pancreatic cancer cell lines, and the inhibitory effects were higher in cells grown in normal 5 mM glucose as compared with cells cultured in 25 mM glucose (19,23,24). It has also been reported that metformin suppresses the IGF-1R and mTOR signaling in pancreatic cancer cells, and this contributes to the antineoplastic activity of this agent (19).…”
Section: Discussionmentioning
confidence: 90%
“…Recent studies report that diabetic cancer patients who take metformin exhibit improved outcomes as compared with patients taking other antidiabetic drugs (10), and this has spurred interest in possible clinical applications of metformin for cancer therapy. One of the hallmarks of metformin action is associated with inhibition of the mTOR signaling in both cancer and non-cancer tissues and cells (15)(16)(17)(18)(19)(20)(22)(23)(24)(25). For exam- A, RNA interference with siRNA against EGFR (siEGFR) decreased cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the mechanism underlying the anticancer effects of metformin remain to be fully elucidated Previous studies have shown that, despite the complexity of the molecular signaling mechanisms of metformin, several critical molecules and pathways have been confirmed to be involved in this regulation, including the activation of AMPK (8,18), inhibition of mammalian target of rapamycin complex-1 (19), interruption of the crosstalk between insulin and insulin-like growth factor-1 receptor (20) and reductions in the expression of vascular endothelial growth factor and plasminogen activator inhibitor-1 (21).…”
Section: Discussionmentioning
confidence: 99%